Human Milk Oligosaccharides Impact Cellular and Inflammatory Gene Expression and Immune Response - Rosa, Fernanda; Sharma, Ashok K.; Gurung, Manoj; Casero, David; Matazel, Katelin; Bode, Lars; Simecka, Christy; Elolimy, Ahmed A.; Tripp, Patricia; Randolph, Christopher; Hand, Timothy W.; Williams, Keith D.; et al. (Frontiers in Immunology, 2022)
Human milk harbors complex carbohydrates, including human milk oligosaccharides (HMOs), the third most abundant component after lactose and lipids. HMOs have been shown to impact intestinal microbiota, modulate the intestinal immune response, and prevent pathogenic bacterial binding by serving as decoy receptors. However, the direct effect of HMOs on intestinal function and immunity remains to be elucidated. To address this knowledge gap, 21-day old germ-free mice (C57BI/6) were orally gavaged with 15mg/day of pooled HMOs for 7 or 14 days and euthanized at day 28 or 35. A set of mice were maintained until day 50 to determine the persistent effects of HMOs. Control groups were maintained in the isolators for 28, 35, or 50 days of age. At the respective endpoints intestinal tissues were subjected to histomorphometric, and transcriptomic analysis while spleen and mesenteric lymph nodes were subjected to flow cytometric analysis. SI crypt was reduced after HMO treatment relative to control at days 28 and 35, while SI villus height and LI gland depth were decreased in the HMO treated mice relative to the control at day 35. We report significant HMO-induced and location-specific gene expression changes in host intestinal tissues. HMOs treatment significantly up-regulated genes involved in extracellular matrix, protein ubiquitination, nuclear transport, and mononuclear cell differentiation. CD4+ T cells were increased in both MLN and spleen, while CD8+ T cells were increased in the spleen at day 50 in the HMOs group in comparison to controls. In MLN, plasma cells were increased in HMOs groups at days 28 and 35 while in the spleen only on day 28 relative to controls. Macrophages/monocytes and neutrophils were lower in the spleen of the HMOs group at days 28, 35, and 50, while in MLNs only neutrophils were lower at day 50 in 14 days HMOs group. In addition, diphtheria toxoid and tetanus toxoid antibody secreting cells were higher in HMOs supplemented group compared to controls. Our data suggests that HMOs have a direct effect on gastrointestinal tract metabolism and immune system even in the absence of host microbiota.